Prospective observational study of the frequency and features of intra-abdominal abscesses in patients with melioidosis in northeast Thailand - Maude, Rapeephan R. (Oxford University Press, 2012)
Retrospective case series from Thailand have reported the presence of intra-abdominal abscesses in around half of patients with melioidosis, a much higher rate than our clinical experience would suggest. We performed a prospective, observational study of 230 adult patients with culture-confirmed melioidosis in which all patients underwent abdominal ultrasound. One or more abscesses were detected in the liver and/or spleen in 77 (33%) cases. These were often multiple (70%, 31/44 in hepatic abscesses and 88%, 50/57 in splenic abscesses) and clinically silent (27% of cases with abscesses presenting with abdominal pain). The mortality rate at 4 weeks post-discharge was lower in patients who were abscess-positive vs abscess-negative (10%, 8/77 vs 20%, 31/153).